2017
DOI: 10.1002/mrm.26645
|View full text |Cite
|
Sign up to set email alerts
|

In vivo MRI of the human finger at 7 T

Abstract: PurposeTo demonstrate a dedicated setup for ultrahigh resolution MR imaging of the human finger in vivo.MethodsA radiofrequency coil was designed for optimized signal homogeneity and sensitivity in the finger at ultrahigh magnetic field strength (7 T), providing high measurement sensitivity. Imaging sequences (2D turbo‐spin echo (TSE) and 3D magnetization‐prepared rapid acquisition gradient echo (MPRAGE)) were adapted for high spatial resolution and good contrast of different tissues in the finger, while keepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…In support of this idea, Cauna and Mannan (30) counted Pacinian corpuscles in the radial half of a foetal index finger and found 178 in total, in almost perfect agreement with Johansson's estimates. More recently, it has been shown that Pacinian corpuscles can be resolved using high-field MRI (31,32), but this technique has not yet been used to establish precise counts. Receptive fields of the type I fibers on the glabrous skin of the hand are small, circular, and well-defined with a mean area of 13 mm 2 for the FAI and 11 mm 2 for the SAI fibers.…”
Section: Glabrous Skin Of the Handmentioning
confidence: 99%
“…In support of this idea, Cauna and Mannan (30) counted Pacinian corpuscles in the radial half of a foetal index finger and found 178 in total, in almost perfect agreement with Johansson's estimates. More recently, it has been shown that Pacinian corpuscles can be resolved using high-field MRI (31,32), but this technique has not yet been used to establish precise counts. Receptive fields of the type I fibers on the glabrous skin of the hand are small, circular, and well-defined with a mean area of 13 mm 2 for the FAI and 11 mm 2 for the SAI fibers.…”
Section: Glabrous Skin Of the Handmentioning
confidence: 99%
“…At each wavelength, 10 8 photons were tracked until detection or their weight reaching 0. The finger geometries simulated were based on an ultrahigh resolution in-vivo MRI image of a human finger, obtained at 7 T with a dedicated finger radio frequency coil [18]. We performed tissue segmentation on the MRI data, resulting in a geometry with a spatial resolution (voxel size) of 0.2 mm consisting of 11 different tissues: bone, cartilage, synovial fluid (SF), synovial membrane (SM), tendon, artery, vein, subcutis, dermis, epidermis, and nerve.…”
Section: Simulationmentioning
confidence: 99%
“…These drawbacks were addressed in [17]. Realistic human joint models and tissue distributions were constructed from an in-vivo MRI scan of a human index finger [18] and used for more detailed simulations of healthy and affected fingers. The realistic finger anatomy involving all finger tissues lead to more reliable simulation results, clarifying if a realistic joint anatomy transmits enough light to enable the detection of RA.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐invasive, more accurate imaging techniques are therefore highly urgent. Magnetic resonance imaging , computed tomography angiography and ultrasound have been reported to visualize skin vasculature, but they have limited resolution which is not high enough to reveal the microvasculature in the superficial layer of skin.…”
Section: Introductionmentioning
confidence: 99%